PELATIHAN ANALISIS LINGKUNGAN BISNIS DAN MANAJEMEN: TREN TEKNOLOGI DAN IMPLIKASINYA BAGI DUNIA BISNIS - Isana S. C. Meranga; Hendra Achmadi; Daniel Ong Kim Kui; Rinto Rain Barry; Margaretha Pink Berlianto (Proceeding National Conference Business, Management, and Accounting (NCBMA), 2026)
Massive technological advancements have fundamentally transformed the global business landscape. These changes not only affect companies’ operational aspects but also reshape how consumers interact, shop, and make decisions. Literacy regarding the impact of technological advancement has become increasingly crucial for younger generations so that they can understand the direction of market changes. This activity aims to provide students of Mahabodhi Senior High School with insights into the importance of business environment analysis in the digital era. Through a narrative approach, participants were encouraged to understand that adaptation to technological advancement is the key to surviving future competition.